Guns and Government - Ginty, Roger Mac. author. aut Link
XVI, 226 p.
Keywords: The book is part of a wider study of the management of contemporary peace processes and has a strong comparative theme. It draws heavily on interviews with key players (politicians and policymakers) in the peace process. Darby and Mac Ginty identify six key strands in the Northern Ireland peace process and assess how factors in each facilitated or obstructed political movement. Chapters are devoted to political change, violence and security, economic factors, external influences, popular responses, and the role of images and symbols.